Administrasi Pendidikan Islam dan Seni Mengelolanya - M Arief Affandi; Abdul Malik Karim Amrullah; Muhammad In'am Esha (STAI Ma'had Aly Al-Hikam Malang, 2022)
This article is oriented to uncover and review the administration development, the formulation of the administration of Islamic education, and the art of managing it. This article examined the literature on the administration of education that usually refers to the west and adapts it to the administration of Islamic education and then manages it with the arts and principles of Islam (Qur'an and Hadith) as well as other Islamic thinkers and the author described it systematically. The results of the article: (1). Development of Islamic education administration through 4 stages (classical organization theory, human relations approach, behavioral science approach, post-behavioral-science approach era), (2). Formulation of Islamic education administration: implementing planning, organizing, staffing, directing, coordinating, reporting, and budgeting which is integrated with the approach of human relationships (meeting the needs of employees, motivation, and the relationship of subordinates and managers) based on Islamic principles. (3). The art of management: strategy (shaping human resources as agents of change in Islam, planning Islamic-based education administration model), implementation (controlling the suitability of planning and implementation, leaders provide motivation, fostering, paying attention to subordinates and participating directly, implications (results and impacts of implementation evaluated and improved) to conform to the principle of continuous improvement.